2018
DOI: 10.1108/ijse-04-2017-0137
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and unemployment exit in Great Britain

Abstract: Structured AbstractPurpose: The aim of this paper is to examine the effect employed friends have on the probability of exiting unemployment of an unemployed worker according to his/her educational (skill) level. Design/Methodology: In common with studies on unemployment duration, this paper use a discrete time hazard model. Findings: The paper finds that the conditional probability of finding work is between 24% and 34% higher per period for each additional employed friend for job seekers with intermediate ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Conversely, a scarcity of scholarly literature exists to scrutinize the influence of social inclusion variables on the mitigation of unemployment. In a study for Great Britain, it was found that post-BREXIT, it was social inclusion that helped reduce unemployment (Sousounis and Lanot, 2018). Similarly, in a study of Spain, it was found across 17 Spanish communities that social inclusion helps enhance skills and abilities and supports people in getting employment (Lechuga et al , 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Conversely, a scarcity of scholarly literature exists to scrutinize the influence of social inclusion variables on the mitigation of unemployment. In a study for Great Britain, it was found that post-BREXIT, it was social inclusion that helped reduce unemployment (Sousounis and Lanot, 2018). Similarly, in a study of Spain, it was found across 17 Spanish communities that social inclusion helps enhance skills and abilities and supports people in getting employment (Lechuga et al , 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%